The Effects of Ambient Temperature on Lumbar Disc Herniation: A Retrospective Study - Wang, Ping; Chen, Cai; Liu, Fanjie; Bu, Fan; An, Jianpeng; Qin, Hao; Zhang, Qinghao; Wang, Tao; Cao, Shengnan; Li, Wei; Shi, Bin (Frontiers in Medicine, 2022)
Purpose: This paper was designed to provide critical evidence into the relationship between ambient temperature and intensity of back pain in people with lumbar disc herniation (LDH). Methods: Data concerning patient’s age, gender, diagnostic logout, admission time, discharge time, residence area, and work area (residence area and work area were used to ensure research area) from 2017 to 2019 was obtained from the Neck-Shoulder and Lumbocrural Pain Hospital in Jinan, China. 1450 hospitalization records were collected in total. The distributed lag non-linear model (DLNM) was used to evaluate the relationship between lag-response and exposure to ambient temperature. Stratification was based on age and gender. Day 1, Day 5, Day 20, Day 28 prior to admission were denoted as Lag 0, Lag 5, Lag 20, and Lag 28, respectively. Results: An average daily temperature of 15-23℃ reduced the risk of hospitalization the most in males. Conversely, temperatures <10℃ drastically increased hospitalization in males, particularly in Lag 0–Lag 5 and Lag 20–Lag 28. Males aged between 40 and 50 years old showed little affect in pain sensation during ambient temperature. Conclusion: High or low ambient temperature can increase the hospitalization risk of LDH, and sometimes, the temperature effect is delayed.